Selling Safely: Cybersecurity Best Practices for Small, Rural Ag Businesses - Lauri M. Baker; Cheryl R. Boyer; Russell Boyer (EDIS)
Cyberattacks are a continued and growing threat for all businesses. Small businesses, like agricultural and rural businesses, should not think they are immune to this threat: obscurity is not security. This new 6-page publication of the UF/IFAS Department of Agricultural Education and Communication includes some cybersecurity best practices and links to resources for further education. Written by Lauri M. Baker, Cheryl R. Boyer, and Russell Boyer. https://edis.ifas.ufl.edu/wc416